Visible-Light-Promoted C(sp3)–H Bond Functionalization toward Aminothiazole Skeletons from Active Methylene Ketones and Thioureas - Zheng, Renhua; Hu, Xiurong; Jiang, Huajiang; Guo, Haichang; Wang, Lei (Synthesis, 2023)
A novel and efficient visible-light-induced method is developed for the one-pot synthesis of functionalized 2-aminothiazoles from easily accessible active methylene ketone derivatives and different thioureas at room temperature. The mild reaction conditions, green chemistry, straightforward work-up, and high yields of the products make this procedure useful for the construction of 2-aminothiazole derivatives.
Keywords: photocatalysis; 2-aminothiazoles; cyclization; free-radical reaction; heterocyclic compounds